Handbook of structural steel connection design and detail - Tamboli, Akbar R. (McGraw-Hill, 1999)
"Featuring a broad range of design methods and details, the Handbook demonstrates the newest techniques and materials in welded joint design and production ... seismically resistant connections ... partially restrained connections ... steel decks ... inspection and quality control ... and more."--BOOK JACKET.